Epigenetic and Phenotypic Responses to Experimental Climate Change of Native and Invasive Carpobrotus edulis - Campoy, Josefina G.; Sobral, Mar; Carro, Belén; Lema, Margarita; Barreiro, Rodolfo; Retuerto, Rubén (Frontiers in Plant Science, 2022)
Despite the recent discoveries on how DNA methylation could help plants to adapt to changing environments, the relationship between epigenetics and climate change or invasion in new areas is still poorly known. Here, we investigated, through a field experiment, how the new expected climate scenarios for Southern Europe, i.e., increased temperature and decreased rainfall, might affect global DNA methylation in relation to phenotypic variation in individuals of clonal plant, Carpobrotus edulis, from its native (Southern African) and invaded (northwestern Iberian Peninsula) area. Our results showed that changes in temperature and rainfall induced phenotypic but not global DNA methylation differences among plants, and the climatic effects were similar for plants coming from the native or invaded areas. The individuals from the Iberian Peninsula showed higher levels of global methylation than their native counterparts from South Africa. We also observed differences between natives and invasive phenotypes in traits related to the pattern of biomass partitioning and to the strategies for water uptake and use and found an epigenetic contribution to phenotypic changes in some leaf traits, especially on the nitrogen isotopic composition. We conclude that the increased temperature and decreased rainfall projected for Southern Europe during the course of the 21st century may foster phenotypic changes in C. edulis, possibly endowing this species with a higher ability to successful cope the rapid environmental shifts. The epigenetic and phenotypic divergence that we observed between native and invasive plants suggests an intraspecific functional variation during the process of invasion. This result could indicate that phenotypic plasticity and global DNA methylation are related to the colonization of new habitats. Our findings reinforce the importance of epigenetic plasticity on rapid adaptation of invasive clonal plants.